Keterkaitan Antara Ilmu Agama dan Ilmu Sosial: : Evolusi Studi Al‐Qur’an dan Tafsir di Indonesia - Nabilah Arju, Asa; Cholillah, Cholillah (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
This research focuses on efforts toward contextualization in the study of the Qur'an and tafsir. The contextualization approach, which is frequently employed by integrating religious studies with contemporary social sciences, often overlooks the core aspects of Qur'anic and tafsir studies. Consequently, this study aims to elucidate the application and forms of integration between religious studies and contemporary social sciences. To achieve this objective, the research employs a qualitative methodology with content analysis as the analytical tool. The central question addressed in this research is: what are the forms of Qur'anic discourse and scientific integration in Indonesia? The findings reveal various forms of integration that can be implemented, such as the re-integration of tafsir studies using contemporary approaches and the reinterpretation of Qur'anic verses through hermeneutics. The application of contemporary methodologies not only yields normative studies but also enhances objectivity and relevance to the current social context. Furthermore, this research underscores the significance of Qur'anic studies in addressing contemporary issues while preserving the scientific integrity of existing core studies.